Building Digital Resilience: Exploring the Narratives of Micro-Entrepreneurs in Technology-Based Financial Transformation in Semarang City - Siti Hidayah; Bagus Kusuma Ardi; Sunarmi Sunarmi; Taufan Akbar Rifky; Shafira Mayada (International Journal of Economics and Management Research, 2025)
This study focuses on designing a technology-based financial restructuring model to address the challenges faced by micro-enterprises in Semarang, particularly in financial management. Micro-enterprises play a vital role in the local economy but often struggle with liquidity issues, delayed payments, and weak receivable management, which increase their vulnerability to financial distress and potential bankruptcy. The research used a qualitative case study approach, combining in-depth interviews with 20 micro-entrepreneurs, five financial experts, participatory observations in 10 businesses, and three Focus Group Discussions (FGDs) involving entrepreneurs, fintech providers, and banking representatives. The data were analyzed using thematic coding, SWOT, and gap analysis to identify financial distress patterns and develop a restructuring prototype through design thinking. The results showed that 80% of MSMEs in Semarang face medium to high financial distress risk, with only 40% using digital tools for financial recording. The findings reveal a significant gap, as 60% of MSMEs still rely on manual methods. The study suggests that integrating basic financial applications and providing digital literacy training can enhance efficiency, decision-making, and resilience. The proposed financial restructuring model addresses both digital solutions and literacy barriers, ensuring practical adoption by micro-entrepreneurs.